PENANGANAN DISMENOREA PRIMER SECARA FARMAKOLOGI DAN NON FARMAKOLOGI PADA REMAJA PUTRI KARANG TARUNA - iga retia (Jurnal Ilmu Kebidanan, 2022)
Background: Dysmenorrhea is pain that is felt with complex symptoms in the form of lower cramps that radiate to the back or legs. Dysmenorrheais divided into 2 types, namely primary dysmenorrhea, namely menstrual pain without any pathology found in the pelvis and secondary dysmenorrhea, namely menstrual pain associated with various pathological conditions in the genital organs. Purpose: To describe the treatment of primary dysmenorrhea in adolescent girls in youth organizations, Cihanjuang Rahayu Village, Parongpong District, West bandung Regency in 2021 Method: This study used a descriptive method. Collecting data by using total sampling with a sample of 100 young women. The research instrument used was a questionnaire. Result: Most of the adolescent girls experienced dysmenorrhea as many as 64 people (64%) and 36 people did not experience dysmenorrhea (36%). Treatment of primary dysmenorrhea pharmacologically as many as 25 people (25%) and non pharmacological treatment as many as 75 people (75%). Conclusion: This study shows that most of the young women experience dysmenorrhea and most of the young women do non pharmacological treatment. Keywords: Dysmenorrhea incidence, dysmenorrhea treatment